Construction of a stable w/o nano-emulsion as a potential adjuvant for foot and mouth disease virus vaccine. (4th July 2017) - Chen, Zenghui; Zhang, Songping; Li, Zhengjun; Ma, Guanghui; Su, Zhiguo
Abstract: A stable and bio-compatible w/o nano-emulsion was developed as adjuvant for foot and mouth disease (FMD) vaccine with isopropyl myristate as oil phase, polyglycerol polyricinoleate, and Tween 80 as surfactants. Dissolving Tween 80 in aqueous phase decreased the droplet size and improved stability of the emulsion through narrowing size distribution, increasing viscosity, and reducing the interfacial tension between oil and water. The nano-emulsion was then formulated with inactivated FMD virus and ovalbumin to investigate its potential application as an adjuvant. Compared with commercial ISA-206 adjuvant, the novel w/o nano-emulsion was able to induce both humoral- and cell-mediated immune response.